2016
DOI: 10.3892/mco.2016.894
|View full text |Cite
|
Sign up to set email alerts
|

Rapid regression of glioblastoma following carmustine wafer implantation: A case report

Abstract: Abstract. Carmustine wafers, which are locally delivered chemotherapy in the form of biodegradable implants, confer a survival benefit to patients with glioblastoma (GB) following surgical resection. While the adverse events of this method, including gas retention and perifocal edema, have been extensively investigated, the immediate efficacy of the implant has rarely been reported. To the best of our knowledge, this is the first reported case of GB in which the tumor rapidly regressed after partial surgical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…However, researchers reported cases of a scalp metastasis within the soft tissue, away from the craniotomy site, such as distal limb, pancreas, spleen, liver, and lung. 1,2 In one report, anterior temporal GBM tumor invaded to sphenoparietal sinus along the greater sphenoid wing causing initial craniotomy after several months which is similar to our case. 8 Extracranial extension glioblastoma tumors occur rarely for several reasons: (1) the absence of lymphatic vessels in the brain; (2) brain sinus structure and number of small pores and direct pathways in the brain; and…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, researchers reported cases of a scalp metastasis within the soft tissue, away from the craniotomy site, such as distal limb, pancreas, spleen, liver, and lung. 1,2 In one report, anterior temporal GBM tumor invaded to sphenoparietal sinus along the greater sphenoid wing causing initial craniotomy after several months which is similar to our case. 8 Extracranial extension glioblastoma tumors occur rarely for several reasons: (1) the absence of lymphatic vessels in the brain; (2) brain sinus structure and number of small pores and direct pathways in the brain; and…”
Section: Discussionsupporting
confidence: 84%
“…6 The findings of some studies showed that by implantation of tumor cells out of the CNS through differentiation by immune cells, tumors can be formed so it seems host immune system control plays an important role in GBM metastasis. 2,4 Results of another study indicated genetic variations can be effective in GBM metastases, such as TP53 mutations, CDKN2A/p16 deletions, epidermal growth factor receptor, or amplifications and allelic losses of chromosomes 1p, 10q, and 19q. 5,8 The Malignancies Research Committee (DTAC) suggests that tumors of low-grade (I, II) glioblastoma have little propensity to develop than high-grade tumors (III, IV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMZ concomitant with and adjuvant to RT is a widely used approach, but the role in elderly cases remains discussed [ 27 ]. Arvold et al stated that the addition of TMZ to RT was associated with a small survival gain [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stea et al conducted a systematic literature review of clinical trials and reports of Gliadel ® wafers in combination with radiation therapy and TMZ, and their findings suggest a positive additive effect without an increase in toxicity [ 132 ]. This warrants the need for larger prospective trials that combine Gliadel ® with TMZ and radiation therapy with scientifically backed study design and patient selection for confirming and establishing the anticipated synergy between these treatments [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ].…”
Section: Invasive Technologiesmentioning
confidence: 99%